Seasonal reproductive allocation in landlocked Alewife Alosa pseudoharengus, in the context of niche construction and eco‐evolutionary feedbacks. Issue 4 (8th May 2022) - Mouchlianitis, Foivos A.; Schultz, Eric T.; Ganias, Kostas
Abstract: The bidirectional dynamics between species and their biotic and abiotic environments, known as eco‐evolutionary feedbacks, may shift the direction of evolution and alter the ecological role of species. Alewife, Alosa pseudoharengus, is an exemplary species to study reciprocal feedbacks between ecology and evolution, owing to repeated independent derivations of a landlocked life history from an ancestral anadromous form. In this study we analysed the reproductive allocation during the spawning season in a landlocked Alewife population in the context of eco‐evolutionary feedbacks. We also compared our findings with previous results from a neighbouring anadromous population of the species. Similarities were found between the two Alewife populations in relation to their ovarian development, oocyte release strategy and fecundity type, but also differences in seasonal patterns of energy investment. Anadromous Alewives invested more in the size of the first oocyte batch of the season and subsequently tapered their reproductive allocation, while spawning batch in landlocked Alewife was invariant as the spawning season progressed. The evolutionary change from ancestral tapering to equitability of seasonal reproductive investment can be explained with reference to eco‐evolutionary changes that occurred upon landlocking related to the availability of zooplankton prey and feeding opportunity.